Moral responsibility of public servants: the essence and directions of improvement (Bulletin of Kharkiv National University of Internal Affairs, 2024)
It is indicated that the moral and ethical side of public servants’ activities is still “terra incognita” for both the national legislator and the scientific community. By comprehending the position of past thinkers, the understanding of the fundamental role of moral and ethical norms in shaping the doctrines of the essence of social responsibility, including such a dimension as moral responsibility, is formed.The choice of one of the ethical norms of behaviour by a public servant is positioned as the quintessence of moral responsibility of public servants. The moral responsibility of public servants is an independent analytical and self-critical activity of a particular public servant based on his/her conscience, as well as on the system of moral and ethical coordinates formed at the level of established and supported by the management practices of daily activities of the staff of a particular public authority, local self-government body, civil society institution, which is embodied in the analysis of their own behaviour and its correlation with the proper moral standard of public servants’ activities. The essence of the moral standard itself is reduced to a model of generally accepted behaviour in Ukrainian society, formed on the basis of administrative and legal legislation, history of the national State-building, moral and ethical values laid down at the level of the principles of public administration, leading trends in scientific and technological progress, acceptable among the population of Ukraine, with due regard for the interests of the main national, racial, linguistic, religious and other minorities. The category of moral and ethical portrait of a public servant is proposed, which is understood as a set of organisational, managerial, institutional, financial instruments and mechanisms for disseminating opinions about a particular public servant and forming social perception at the level of the entire population or a certain part of it (service recipients, representatives of a region, field of activity, organisation) regarding the role, functions, purpose (vocation) and activities of such a public servant in general.In order to introduce high moral standards into the activities of domestic public servants, the following areas of improvement of their activities in the context of moral responsibility are proposed: restructuring of public morality in the context of understanding the activities of whistleblowers; increasing the authority of public authorities; development and adoption of the Code of Ethics for Public Servants at the national level.